2021
DOI: 10.3390/geosciences11050215
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Phenomena Induced by the 26 November 2019, Mw = 6.4 Durrës (Albania) Earthquake and Liquefaction Susceptibility Assessment in the Affected Area

Abstract: On 26 November 2019, an Mw = 6.4 earthquake struck the central-western part of Albania. Its impact comprises secondary earthquake environmental effects (EEE) and severe building damage within the Periadriatic and the Tirana Depressions. EEE comprised mainly liquefaction phenomena in coastal, riverine, and lagoonal sites of the earthquake-affected area. From the evaluation of all available earthquake-related data, it is concluded that liquefaction sites are not randomly distributed within the affected area but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Such areas are particularly vulnerable to the triggering of liquefaction phenomena, as has been demonstrated and highlighted in cases of other recent earthquakes in the Balkan Peninsula, where lateral spreading and sand boils have occurred in abandoned meanders and old riverbeds. Similar examples of liquefaction manifestations have been recently presented by Mavroulis et al [62] in the earthquake-affected area of Durrës (Albania) due to the 26 November 2019 Mw = 6.4 earthquake and by Papathanassiou et al [63] in the Pineios and Titarissios River beds due to the 2021 Thessaly (central Greece) Mw = 6.3 earthquake. In both cases, based mainly on field observations and mapping of the earthquake-triggered liquefaction phenomena, it is concluded that most of them were generated where river channels had been reclaimed or in abandoned and filled channels.…”
Section: Antakyasupporting
confidence: 79%
See 1 more Smart Citation
“…Such areas are particularly vulnerable to the triggering of liquefaction phenomena, as has been demonstrated and highlighted in cases of other recent earthquakes in the Balkan Peninsula, where lateral spreading and sand boils have occurred in abandoned meanders and old riverbeds. Similar examples of liquefaction manifestations have been recently presented by Mavroulis et al [62] in the earthquake-affected area of Durrës (Albania) due to the 26 November 2019 Mw = 6.4 earthquake and by Papathanassiou et al [63] in the Pineios and Titarissios River beds due to the 2021 Thessaly (central Greece) Mw = 6.3 earthquake. In both cases, based mainly on field observations and mapping of the earthquake-triggered liquefaction phenomena, it is concluded that most of them were generated where river channels had been reclaimed or in abandoned and filled channels.…”
Section: Antakyasupporting
confidence: 79%
“…Additionally, scree is also presented in areas with a large slope along the mountain front [64]. Regarding hydrogeology, the area is characterized with a high groundwater level ranging from 0-6 m to 15 m or more [62]. From the active tectonics viewpoint, the residential area of the Ahir Mt front is disrupted by E-W striking faults that have produced surface ruptures during the last 11,000 years, while the northern boundary of the city has also been disrupted by faults that are suspicious for Holocene activity [14] (Figure 20).…”
Section: Kahramanmarasmentioning
confidence: 99%
“…During the last two decades, several moderate earthquakes M > 5.0 have hit Durrës, mentioning the 5 September 2007 (4.8-5.0) and the 4 July 2018 (M w 5.1) earthquakes. The last seismic activity, resulting in the strongest instrumental recorded seismic activity during the last four decades in this region, started on 21 September 2019 (M w 5.6), located 3-km west of Shijak, subsequently followed, after 10 min, by an M w 5.1 aftershock (Figs 2 and 3;Aliaj 2020;Papadopoulos et al 2020;Mavroulis et al 2021;Anton et al 2022). The main shock and seismic sequence aftermath caused severe damage to local building environments.…”
Section: Instrumental Seismicitymentioning
confidence: 98%
“…The 1964 magnitude 9.2 earthquake in Alaska and the magnitude 7.6 earthquake in Niigata of the same year, prompted extensive research on this phenomenon. Soil liquefaction has also been observed in recent earthquakes in China [1], Japan [2], Indonesia [3] and the USA [4,5].…”
mentioning
confidence: 99%